Використання методів багатокритеріальної оптимізації для вибору телекомунікаційного обладнання - Скорик, Ю. В.; Ліннік, М. В. (ХНУРЕ, 2025)
The paper considers theoretical and practical aspects of the application of multi-criteria optimization methodology to select design solutions that are optimal according to a set of dependent and contradictory quality indicators, in particular, for L2 level managed switches taking into account 5 quality indicators: price; number of ports; number of combined ports; buffer memory capacity, throughput; number of forwarded packets. At the same time, a Pareto subset of 22 valid variants is first selected, which included 9 variants. The remaining variants of the system are unconditionally the worst and are excluded from further consideration. Then, the Pareto subset is narrowed down to a single system variant by methods based on the theory of fuzzy sets, utility theory, and lexographic method.
Keywords: телекомунікаційне обладнання; багатокритеріальна оптимізація